2009
DOI: 10.1002/jms.1638
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric analysis of the glycosphingolipid‐derived glycans from miniature pig endothelial cells and islets: identification of NeuGc epitope in pig islets

Abstract: Glycosphingolipid (GSL) is a major component of the plasma membrane in eukaryotic cells that is involved directly in a variety of immunological events via cell-to-cell or cell-to-protein interactions. In this study, qualitative and quantitative analyses of GSL-derived glycans on endothelial cells and islets from a miniature pig were performed and their glycosylation patterns were compared. A total of 60 and 47 sialylated and neutral GSL-derived glycans from the endothelial cells and islets, respectively, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…There are considerable differences in the expression of Neu5Gc across pig cells and tissues . It is clear that Neu5Gc is highly expressed on the surface of endothelial cells and pancreatic islet cells .…”
Section: Discussionmentioning
confidence: 99%
“…There are considerable differences in the expression of Neu5Gc across pig cells and tissues . It is clear that Neu5Gc is highly expressed on the surface of endothelial cells and pancreatic islet cells .…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [12] investigated several glycan-binding proteins that were involved in xenograft rejection. Additionally, Kim et al [10,11] showed that 60 and 47 glycosphingolipids derived glycans and N-glycans were present in miniature pig endothelial cells and islets. In summary, expression of various gangliosides in the liver and heart of NIH-miniature pigs can activate both the innate and adaptive immune response; therefore, the targeting of these gangliosides will be an attractive avenue in the development of techniques to control graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al. reported comprehensive porcine glycomes from various sources using mass spectrometry . The study included the N‐glycome from a specific pathogen‐free Chicago Medical School miniature porcine kidney as a model of porcine endothelial cells.…”
Section: Differences In the Glycome Between Human And Pigmentioning
confidence: 99%
“…Kim et al. identified 62 glycolipid‐derived glycans from porcine endothelial cells, and 48 glycans were detected from porcine islet cells . A potential α‐Gal neolactose sequence (Hex 4 HexNAc 1 ) was quantified by mass spectrometry in both cells (Table S4).…”
Section: Differences In the Glycome Between Human And Pigmentioning
confidence: 99%
See 1 more Smart Citation